Сравнительный анализ антенн с различными отражателями для базовых станций стандарта GSM - Шило, Б. А. (ХНУРЭ, 2012)
This report provides a comparative evaluation of the collinear antenna with flat reflector, with a parabolic mirror and angled on the basis of the calculated radiation patterns of antennas. Collinear antenna arrays are widely used for the construction of antenna systems of base stations, including omniirectional and sector antennas via GSM